Efeitos de diluição química nos compostos intermetálicos TRNi3Ga9 (TR = Gd, Tb, Dy, Ho e Er) - Mendonça, Edielma Costa (2019)
In this work, the structural and magnetic properties of RENi3Ga9 (RE = Gd, Tb, Dy, Ho and Er) intermetallic compounds doped with yttrium grown using the Ga metal flux method are studied. X-ray diffraction (XRD) measurements are performed for all the samples. The analysis of structural data through Rietveld method indicate that a single phase with trigonal crystalline structure and spatial group R32 is formed for all the samples. Besides, despite the crystal structure is unaffected by yttrium substitution a monotonic decreases of lattice parameter is observed. The magnetic susceptibility measurements show, for all compounds, an antiferromagnetic behavior with a systematic decrease of the Neel temperature as a function of the doping extrapolating to zero at x = 0.85, 0.66, 0.81 and 0.94 for the compounds of Gd , Tb, Dy and Ho, respectively. This behavior can also be confirmed from the specific heat measurements. Because the Dy compounds exhibit a complex magnetic behavior for T < TN their magnetic properties are studied with more details. Electronic Spin Resonance (ESR) measurements are taken for the compounds Gd1-xYxNi3Ga9 (0 ≤ x ≤ 0.90) in the temperature range 15 ≤ T ≤ 300 K. The line shapes show to be a single Dysonian line coming from Gd3+ ions with values of g independent of temperature. The line widths follow the Korringa-like behavior as a function of temperature for all samples. The Korringa rates (b = ΔH/ΔT) show a dependence with the Y-concentration indicating a “bottleneck” regime. For the more dilute sample (x = 0.90) when it is believed that the bottleneck effects are minimized, we calculate the effective exchange parameters dependent on q between the localized moments of the Gd3+ ions and the conduction electrons . The compounds of RE1-xYxNi3Ga9 (RE = Tb, Dy, Ho and Er and x = 0.15 and 0.30) show a strong anisotropic effect evidenced by the large ratio of Xeasy/Xhard at TN. This fact is likely related to the strong effects of crystalline electric field (CEF). The evolution of the crystalline field schemes for each R is studied using a mean-field model that includes the Ruderman-Kittel-Kasuya-Yosida anisotropic exchange interaction (RKKY) and a trigonal CEF Hamiltonian. Our results show that the magnetic dilution takes an important role in determining the magnetic behavior of compounds, that is, the weakening of the RKKY exchange interactions and the change in the crystalline electrical field effect of these compounds.